2009
DOI: 10.1119/1.3065023
|View full text |Cite
|
Sign up to set email alerts
|

A national study assessing the teaching and learning of introductory astronomy. Part I. The effect of interactive instruction

Abstract: We present the results of a national study on the teaching and learning of astronomy as taught in general education, non-science-major, introductory astronomy courses. Nearly 4000 students enrolled in 69 sections of courses taught by 36 different instructors at 31 institutions completed ͑preand post-instruction͒ the Light and Spectroscopy Concept Inventory ͑LSCI͒ from Fall 2006 to Fall 2007. The classes varied in size and were from all types of institutions, including 2-and 4-year colleges and universities. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 27 publications
5
59
0
Order By: Relevance
“…Standardized assessment practices in undergraduate physics education emphasize the use of conceptual pre-and post-tests ("concept inventories")-the outcomes of which have been used to inform changes to curriculum design and instructional practices [5]. A wide variety of studies have been conducted using concept inventories [6][7][8][9][10][11][12][13], and student learning outcomes on such assessments are well documented [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Standardized assessment practices in undergraduate physics education emphasize the use of conceptual pre-and post-tests ("concept inventories")-the outcomes of which have been used to inform changes to curriculum design and instructional practices [5]. A wide variety of studies have been conducted using concept inventories [6][7][8][9][10][11][12][13], and student learning outcomes on such assessments are well documented [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-and post-instructional testing with concept inventories have become a common method for assessing physics and astronomy teaching and learning on a large scale, leading to profound insights and evidence for the success of curriculum reform. [6][7][8][9][10][11][12][13] In this paper, we build on this literature and provide a new tool for assessing changes in introductory algebra-based students' conceptual understandings and reasoning about gravity-the Newtonian Gravity Concept Inventory (NGCI).…”
Section: Introductionmentioning
confidence: 99%
“…Most physics students are science majors and have had previous instruction in astronomy or physics, whereas astronomy students are primarily non-science majors who take the course as a one-time general education science requirement before going on to become society's journalists, politicians, lawyers, historians, business leaders, and teachers. 11,16 Also, the typical physics course investigates Newtonian gravity within a very different context than the astronomy course. (The astronomy curriculum emphasizes gravity in the context of planet and star formation, space travel, the structure of galaxies, and the evolution of the universe.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more than one study, students who worked in groups showed significantly greater gains on conceptual questions than students who In the domain of the introductory astronomy survey course college students often take to fulfill a general education distribution requirement common among most US universities teaching, one of the most widespread active learning instructional pedagogies that leverages collaborative learning is arguably lecture-tutorials which is used by more than 30,000 students each year (Prather, Slater, Bailey, Jones, & Dostal, 2005). Funded by several NSF awards, Lecturetutorials (Prather, Slater, Adams, & Brissenden, 2012) are collaborative learning activities that have become very popular for use in general education introductory astronomy courses (Prather, Rudolph, Brissenden, & Schlingman, 2009). Essentially short student worksheets are carefully designed for students to work with and discover the conceptual power of scientific models for themselves rather than being lectured to about them.…”
Section: Collaborative Learning and Lecture-tutorials For Introductormentioning
confidence: 99%